Programa para la reducción de pérdidas del suministro de agua potable de la empresa de servicios públicos de Paipa S.A.S Red Vital E.S.P (2021)
Optimization of the drinking water supply service is important for the Red Vital Aqueduct Company of the municipality of Paipa. During the course of 2017, a study of losses in the drinking water distribution network was carried out, which showed losses in the aqueduct system of approximately 50%. Therefore, there is a need to formulate a loss program through which optimization in the distribution network and improvements in service provision are guaranteed. The program is carried out by proposing a general methodology adjusted from existing elements in the company such as data, records and counters in order to propose seven projects that will help minimize losses based on the strategies proposed by the National Department of Planning using the Adjusted General Methodology MGA